The Use of Deixis in “Five Feet Apart” Movie - Widayanti, Ni Ketut Feni Kresna; Ediwan, I Nyoman Tri (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This article entitled “The Use of Deixis in “Five Feet Apart” Movie” the study aims to analyze the types of deixis used in the